Invasive pulmonary aspergillosis in patients with influenza infection: report of two cases and systematic review of the literature. (February 2014) - Alshabani, Khaled; Haq, Athar; Miyakawa, Ryo; Palla, Mohan; Soubani, Ayman O
<x xml:space="preserve">Abstract</x> Superinfection or coinfections are major causes of morbidity and mortality in patients with influenza. There are limited data on invasive pulmonary aspergillosis (IPA) in this setting. We conducted a systematic review of the literature for patients with IPA following influenza infection. A total of 68 patients (two reported from our institution and 66 identified by literature review) were analyzed. The majority of patients had underlying comorbid illnesses. Overall, the mortality rate in this cohort was 47%. On multivariate analysis, H1N1 infection was associated with better outcome (odds ratio [OR]: 0.19; 95% CI: 0.05–0.67; p = 0.010), whereas corticosteroid therapy during hospitalization was associated with worse outcome (OR: 13.5; 95% CI: 3.65–49.67; p < 0.0001). In conclusion, IPA is an emerging serious infection in patients with influenza. A high index of suspicion is necessary for the timely identification and treatment of these patients.